Impact of project-based learning in the human reproductive system to the students self-regulated learning in SMA Negeri 1 Bantul - Asta puji utami (Jurnal Kependidikan Penelitian Inovasi Pembelajaran, 2023)
This study aims to determine the effect of project-based learning models on Human Reproductive Systems material on the learning independence of students at SMAN 1 Bantul. This research is a quasi-experimental quantitative research using the nonequivalent control group design. The sampling technique was cluster random sampling. Learning independence data was obtained using a questionnaire based on six aspects, namely independence of others, having self-confidence, behaving in discipline, having a sense of responsibility, behaving based on one's own initiative, and exercising self-control. Data were analyzed descriptively and inferential. Descriptive analysis was performed to show the mean value, standard deviation, and percentage. Inferential analysis using the T-test of independent data, to show the difference in the value of independent learning between the experimental and control classes. This inferential analysis is carried out after it is known that the prerequisites of the parametric inferential statistical test are met. The results showed that the average value of students' learning independence in the experimental class was 74.3611. While the control class is 72.2667, so it can be concluded that there is a positive and significant influence on the project-based learning model with student learning independence, which is indicated by the value of tcount ttable, namely 2.815 1.666.Keywords: Project-Based Learning Model, Student Independence, Human Reproductive                         System